Enjeux expérientiels de l'utilisation de l'IA en anatomopathologie - Laurent Collet; Michel Durampart; Laurent Heiser; Ludovic Picard (Communiquer)
This article is based on a research conducted in a medical office of anatomo-cytopathology, and focuses on the transformations of the work of diagnostic analysis of prostate tissue in a context of integration of a diagnostic support software based on Artificial Intelligence (AI). Researchers in information and communication sciences were interested in the experience of eight doctors from this office during the AI software test phase, i.e. in the subjective sense that these individuals attribute to their activities, in a critical perspective of emancipation (such as increasing their knowledge and know-how) versus alienation (reduction of knowledge and know-how through technical rationalization) in the context of changes in their work habits.